Alat Pemberi Pakan Udang dan Pemantau Kekeruhan Air yang Dilengkapi dengan Filter Air dan Sistem Penggantian Air Menggunakan WeMos D1 R1 Berbasis Internet of Things - Alwi Ristanta; Abdul Jabbar Lubis; Risko Liza; Dodi Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In a shrimp farming area, several things appear. Where shrimp farming jobs still use traditional methods or work manually so they need a lot of time. Shrimp farming is an entrepreneur with long production results, so hereby collect some of the main problems experienced by shrimp farmers. The author conducts research to support businesses to operate effectively, efficiently and practically. It is known that shrimp farmers have little difficulty in maintaining feed. Therefore, the authors designed a feeder and water turbidity monitor that can work automatically based on the feeding schedule and the level of water turbidity. This shrimp feeder and water turbidity monitor uses the WeMos D1 R1 microcontroller which is the main control center, uses the Blynk application to control the tool, and uses servo motors, sensors, filters and other components. By using these components and some software that supports the tool, shrimp feeders and water turbidity monitors can work automatically according to a predetermined schedule, and are able to send notifications to Blynk when the tool finishes the work process